(untitled) (International Journal of Social Science, Commerce & Management Studies, 2026)
Urban youth are a central player in climate change solutions, both as a generation who are facing the brunt of climate change and as a generation who has the power to drive transformative change by their purchasing power, civic engagement, and social influence. The relationship between awareness of climate change and sustainable actions among urban youth. Based on the research literature from three disciplines (environmental psychology, education research and sustainability science), the paper is concerned with the common assumption that there is a simple and straightforward correlation between knowledge about climate change and sustainable behavior. The review is organized in four main analytical dimensions (conceptual dimensions of awareness and behaviour, sources and determinants of climate knowledge, psychological and social mediators to pro-environmental behaviour, and observed climate behaviour outcomes). One key and constant finding is that despite the high climate change awareness among many urban youth, there is still a lack of knowledge-action gap, in the sense that this awareness does not necessarily lead to a change in pro-ecological behaviour in everyday life. The difference is explained in terms of perceived behavioural control, social norms, emotional reactions (eco-anxiety and hope), structural and infrastructural barriers, influences of digital media and influences of peer network. The review finds that the awareness alone is not enough to promote sustainable behaviours, and that a change of the enabling environment is necessary, with interventions focusing on motivation and capability. Future research directions are suggested, such as longitudinal, cross-cultural and intersectional study as well as the development of emerging digital and educational interventions.